Неравномерности в распределении метана в угольных пластах - Алексеев, А.Д.; Фельдман, Э.П. (Физико-технические проблемы горного производства, 2008)
Обчислено термодинамічний потенціал Гіббса вугільного пласта, який розглядається як твердотільний каркас разом з газом метаном. У явному вигляді знайдена залежність пружної енергії пласта від тиску газа, пружних модулів та пористості вугілля. Мінімізація потенціала Гіббса по відношенню до перерозподілу газа дала можливість встановити ділянки пласта, де відбувається підвищення тиску газа, а також оцінити відносну зміну тиску на у цих ділянках при збільшенні нагрузки на пласт. Одержані результати можуть бути основою прогнозу локалізації викидонебезпечних ділянок пласта. We have calculated Gibbs thermodynamic potential of a coal bed that is considered as a solid-state framework filled with gaseous methane. We have found the explicit dependence of the elastic energy of the bed on the gas pressure, elastic modules and coal porosity. The minimization of Gibbs potential with respect to gas redistribution gave us an opportunity to establish the parts of the bed where the increase of the gas pressure took place and to estimate relative change of the pressure located there at the growing loading of the bed. The obtained results can be the basis of the predictive localization of the parts of the bed dangerous with respect to outbursts.